Assessment of frequency, risk category and intervention needs in psychoactive drug users by using WHOASSIST Questionnaire among medical students in Karachi - Humaira Mehmood; Madiha Shafi; Shams ul Arifin Qasmi; Muhammad Saeed Afsar; Samina Mohsin; Qurat-Ul-Ain (Journal of the Pakistan Medical Association, 2022)
Objectives: To determine the frequency of use of various psychoactive drugs among medical students in an urban setting, and to assess the risk category and intervention needs. Methods: The descriptive cross-sectional study was conducted from January to June 2018 at four medical education institutions of Karachi; 2 each randomly selected from registered public and private sectors. From the clinical classes of each institution, fourth year was randomly chosen by lottery method. Data was collected using the Alcohol, Smoking and Substance Involvement Screening Test version 3.0. Data was analysed using SPSS 20. ---Continue